Review of Power Systems of Non-Thermal Plasma Reactors and Their Applications - Stryczewska, Henryka Danuta; Komarzyniec, Grzegorz Karol; Boiko, Oleksandr (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
Atmospheric pressure cold plasma has recently attracted considerable scientific interest and found a range of practical applications. Common sources of such plasma include dielectric barrier discharge (DBD), atmospheric pressure plasma jets (APPJ), and gas arc discharge (GAD). Various nonlinear phenomena occurring within the power supply–plasma reactor system – such as harmonic generation, resonance and ferroresonance, switching overvoltages, and pulse formation – can, when properly managed, enhance reactor performance. These effects contribute to more reliable plasma ignition, increased process efficiency, and improved integration of the plasma system with the electrical grid. The examples of power supplies used in plasma processes in power generation, environmental engineering, agriculture and medicine presented in this review confirm the above statement.